Organizational Effects of Estrogens and Androgens on Estrogen and Androgen Receptor Expression in Pituitary and Adrenal Glands in Adult Male and Female Rats - Lagunas, Natalia; Fernández-García, José Manuel; Blanco, Noemí; Ballesta, Antonio; Carrillo, Beatriz; Arevalo, Maria-Angeles; Collado, Paloma; Pinos, Helena; Grassi, Daniela (Frontiers in Neuroanatomy, 2022)
Sex steroid hormones such as androgens and estrogens are known to exert organizational and activational action on the brain and peripheral tissues for the establishment of the biological axis in charge of regulating behaviors such as reproduction and stress and emotional responses. Estradiol, testosterone, and their dependent metabolites exert their biological action by activating genomic mechanisms that include the recruitment of the canonical receptors such as estrogen receptor (ER), ER, androgen receptor (AR) and by no-genomic mechanisms that involve the activation of membrane receptors such as the G couple estrogen receptor (GPER). Expression of ERs and AR was found be different between males and females both in the brain and peripheral tissues suggesting a sex-dependent regulation of their expression and function. Therefore, studying the ERs and AR distribution and expression levels is key to understand the central and peripheral role of sex steroids in the establishment of the sex-specific behaviors in males and females. We investigated the organizational effects of estrogens and androgens on ERs and AR expression levels in the pituitary and adrenal glands of male and female rats by I) inhibiting the androgen pathway, selectively blocking the AR with flutamide, II) fostering the estrogen pathway, either selectively inhibiting the aromatase with letrozole or selectively blocking the 5α-reductase with finasteride. Data show that inhibition of DHT and E2 production during the first week critical period mainly decreases the ERs in male to female values and AR in female to male levels with a net result of masculinization of the female and feminization of males in the pituitary gland and increases AR in female to male levels, masculinizing the adrenal system whereas blockage of androgens’ action, differentially modulates the ERs in males and females and decreases AR in both males and females in the two glands. All together the results suggest that neonatal modifications of the androgen and estrogen pathways can potentially lead to permanent modifications of the neuroendocrine functions of the pituitary and adrenal glands in the adulthood of both sexes.